The Letters of Mary Penry : A Single Moravian Woman in Early America - Penry, Mary, 1735-1804 (Book collections on Project MUSE., 2018)
"A collection of letters by Mary Penry (1735-1804), who immigrated to America from Wales and lived in Moravian communities for more than forty years. Offers a sustained view of the spiritual and social life of a single woman in early America"--Provided by publisher.